بنود استبانة الفعالية الذاتية في مهارة الكتابة باللغة العربية لغة ثانية: ملاحظات وإعادة النظر / SELF-EFFICACY QUESTIONNAIRE ITEMS IN ARABIC WRITING SKILL AS A SECOND LANGUAGE: OBSERVATIONS AND RECONSIDERATION - Nadwah Hj Daud; Farhana Ghazudin; Majdi Hj. Ibrahim (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2022)
مُلخَّص البحث: تنظر هذه المقالة إلى إعادة النظر لبنود الفعالية الذاتية في مهارة الكتابة باللغة العربية لغة ثانية؛ لأنه من المفترض أن البنود التي توضع لتقويم الفعالية الذاتية حسب المهارات اللغوية للغة الهدف، وذلك لكون المهام مصممة لمهارة لغوية معينة؛ لذا تفيد هذه المقالة أفكار أساسية فيما يلزم مراعاته أثناء تصميم استبانة لتقويم الفعالية الذاتية في مهارة الكتابة باللغة العربية لغة ثانية. تبنّت هذه المقالة دراسة قام بها المؤلفون سابقاً؛ حيث وجدوا بأن الدراسة هيّأت إلى القضية أي أن البنود في الدراسة لا بد من صياغتها، وأنه من المستلزم أن يتعلق محتواها بالمهام. الكلمات المفتاحية: الفعالية الذاتية في اللغة الثانية، الفعالية الذاتية في الكتابة باللغة العربية، أبعاد الفعالية الذاتية لمهارة الكتابة، خصائص الفعالية الذاتية، صياغة بنود الفعالية الذاتية في مهارة الكتابة. Abstract This article is looking at reconsidering items for a questionnaire of self-efficacy in Arabic writing skill as a second language. It is assumed that different items should serve different language skill of target language. This is due to the assigned tasks are designed specifically for one language skill. This article suggests basic ideas on what to consider during desigining a questionnaire of self-efficacy in Arabic writing skill. This writing is particularly based on study of self-efficacy in Arabic writing skill as a second language run previously by the authors where they found that it has prompted a need to formulate the said items and the content of items should always be based on the tasks assigned to learners. Keywords: self-efficacy in second language, self-efficacy in Arabic writing, self-efficacy dimension in writing skill, self-efficacy features, writing efficacy phrases Abstrak Artikel ini bertujuan mempertimbangkan semula item soal-selidik keberkesanan kendiri untuk kemahiran menulis dalam Bahasa Arab sebagai bahasa kedua. Mengikut andaian setiap item soal-selidik menyasarkan kemahiran bahasa yang berbeza dalam bahasa sasaran. Ini disebabkan oleh tugasan yang diberikan adalah direka khusus untuk satu kemahiran bahasa. Artikel ini mencadangkan beberapa perkara asas yang perlu dipertimbangkan semasa mereka bentuk item-item soal-selidik keberkesanan kendiri dalam kemahiran menulis bahasa Arab. Sesungguhnya makalah ini adalah hasil pemerhatian terhadap yang terdahulu oleh para penulis di mana mereka mendapati terdapat keperluan untuk merumuskan semula item-item tersebut serta kandungan item hendaklah sentiasa menepati bentuk tugasan yang diberikan kepada pelajar. Kata kunci: keberkesanan kendiri dalam bahasa kedua, keberkesanan kendiri dalam penulisan Bahasa Arab, dimensi keberkesanan kendiri dalam kemahiran menulis, ciri-ciri keberkesanan kendiri, frasa-frasa menampilkan keberkesanan kendiri